2014
DOI: 10.1177/2158244014522072
|View full text |Cite
|
Sign up to set email alerts
|

Youth and Ethnic Movements and Their Impacts on Party Politics in ECOWAS Member States

Abstract: Although they historically played a pivotal role in the fight against colonial rule-as they have in recent attempts to entrench multiparty democratic processes-the role of youth in political parties in West Africa has received less than commensurate attention in studies on democratization. Unlike in advanced democracies where parties are key agents of political socialization and leadership, parties in West Africa are built on ethno-religious foundations. A peculiar character of highly marginalized youth thus b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 10 publications
(15 reference statements)
0
34
0
Order By: Relevance
“…In the case of Nigeria, Dike (2014) and Olaiaya (2014) observed that, the youths who are involved in the activities of the Boko Haram militancy against the Nigerian government do so as a result of unemployment, some as a result of illiteracy and driven by poverty, they find themselves engaging in the Boko Haram activities such as bombing of private and public facilities and killing of innocent lives. Thus, it is the responsibility of the West African states to focus on good governance in order to improve on the social conditions of their people and citizenry.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Nigeria, Dike (2014) and Olaiaya (2014) observed that, the youths who are involved in the activities of the Boko Haram militancy against the Nigerian government do so as a result of unemployment, some as a result of illiteracy and driven by poverty, they find themselves engaging in the Boko Haram activities such as bombing of private and public facilities and killing of innocent lives. Thus, it is the responsibility of the West African states to focus on good governance in order to improve on the social conditions of their people and citizenry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lindberg (2001) argued that, trade can be seen as a main function of states which can be conducted by the private sector in negotiation with the state; it is then expected of the state to provide the needed strategies that would enhance economic governance towards services that can be provided to the people as well as public governance leading to the security of the people. Issues such as unemployment, poverty, illiteracy, as well as poor governance are the main challenges that may lead to youth's engagement in activities such as militancy and insurgency against the government of a given state like in the case of Nigeria, Mali, Niger, and Liberia (Dike, 2014;Olaiaya, 2014;Yusuf, 2013;Aghedo, 2012;Salaam, 2012;Jackson, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For African countries to succeed or move forward an environment free of insecurity remains the first goal and that is the reason NEPAD has outlined her set goals where the said subject is listed first among other priorities (NEPAD, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In achieving this goal, NEPAD partners with the Federal Ministries, Departments and Agencies at the national level on how best issues relating to insecurity challenges can be resolved, other stakeholders of NEPAD includes the integration of the State and Local Governments, the Civil Society Organizations, the Private Sector, and as well as the international community to engage in strategies that would lead to conflict prevention, conflict management and resolution (NEPAD, 2001;NEPAD Nigeria, 2010 andNEPAD Nigeria, 2015). It is very important then to understand that without peace and security, the NEPAD objectives of partnering with other countries within and outside Africa becomes very difficult, and that is the major focus of this paper which is to proffer solutions to the issues that are presently facing Nigeria as a State in Africa, considering the insecurity challenges posed by the Boko Haram militants since 2009.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation